Visual Outcome of Descemet Membrane Endothelial Keratoplasty during the Learning Curve in Initial Fifty Cases - Sanjay K. Singh; Sanjeeta Sitaula (Journal of Ophthalmology)
This study was performed to evaluate the clinical outcomes of the first fifty patients who underwent Descemet membrane endothelial keratoplasty (DMEK) during the 3-month postoperative period and to describe the challenges encountered during the learning curve. In this retrospective study, we reviewed the charts of patients who underwent DMEK. All information regarding patient demographics, indication for surgery, preoperative and postoperative visual acuity at 3 months, donor age, and complications encountered intraoperatively and postoperatively was recorded. Donor endothelial cell count at the time of surgery and during the 3-month follow-up was noted. Data were analyzed using SPSS version 17. Fifty eyes of 49 patients were included in the study with majority being female patients (male : female = 2 : 3). Mean age of patients was 56.8 ± 11.4 years with the age range of 22–78 years. The common indications for DMEK were pseudophakic bullous keratopathy –57.1%, Fuchs endothelial dystrophy-34.7%, failed grafts-6.1% (Descemet stripping endothelial keratoplasty (DSEK) and failed penetrating keratoplasty), and others. Preoperative best spectacle-corrected visual acuity was <20/400 in 88% cases. Postoperative best spectacle-corrected visual acuity at 3 months was >20/63 in 41.8% of the cases, and 93% had visual acuity of 20/200 or better. Donor size was 8 mm, and average donor endothelial cell count (ECC) was 2919 ± 253 cells/mm2. Average ECC at 3 months postoperatively was 1750 ± 664 cells/mm2, which showed a 40% decrease in ECC. The most common encountered complication was graft detachment, which occurred in 16% cases for which rebubbling was done. Regular follow-up and timely identification of graft detachment may prevent the need for retransplantation.